2019
DOI: 10.1111/oik.06067
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of extra food to reproduction depend on maternal condition

Abstract: The amount of food resources available to upper‐level consumers can show marked variations in time and space, potentially resulting in food limitation. The availability of food resources during reproduction is a key factor modulating variation in reproductive success and life‐history tradeoffs, including patterns of resource allocation to reproduction versus self‐maintenance, ultimately impacting on population dynamics. Food provisioning experiments constitute a popular approach to assess the importance of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 111 publications
0
45
0
Order By: Relevance
“…In birds, conditions favouring intraspecific brood parasitism may include limitation of female ability to breed in adverse environmental conditions, clutch loss due to predation during egg laying, the occurrence of alternative reproductive tactics, or simply the occurrence of constraints in obtaining a breeding territory or mate (see Lyon and Eadie 2008 for a detailed review). In our lesser kestrel population, clutch loss due to predation is extremely rare, and in the study year the ecological conditions were generally favourable (Podofillini et al 2019). The occurrence of intraspecific brood parasitism may thus be explained by the presence at the colony of prospecting yearling females, which mostly do not breed despite being sexually mature (Hiraldo et al 1996).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In birds, conditions favouring intraspecific brood parasitism may include limitation of female ability to breed in adverse environmental conditions, clutch loss due to predation during egg laying, the occurrence of alternative reproductive tactics, or simply the occurrence of constraints in obtaining a breeding territory or mate (see Lyon and Eadie 2008 for a detailed review). In our lesser kestrel population, clutch loss due to predation is extremely rare, and in the study year the ecological conditions were generally favourable (Podofillini et al 2019). The occurrence of intraspecific brood parasitism may thus be explained by the presence at the colony of prospecting yearling females, which mostly do not breed despite being sexually mature (Hiraldo et al 1996).…”
Section: Discussionmentioning
confidence: 73%
“…Extra food did not significantly affect SMI or morphology (F 1,68 < 2.91, p > 0.09); these models also revealed that females had significantly shorter tarsi (F 1,68 = 5.97, p = 0.02) and larger SMI (F 1,67 = 51.35, p < 0.001) as compared to males (see Podofillini et al 2019 for further details). Twoway interactions between food supplementation and sex were not significant (F 1,66 < 1.78, p > 0.19).…”
Section: Resultsmentioning
confidence: 81%
“…The lesser kestrel is a sexually dimorphic species, females being ca. 15% heavier than males [54]. Females lay up to 5 eggs that both parents incubate for ca.…”
Section: Target Species Study Area and General Field Methodsmentioning
confidence: 99%
“…7 and ca. 14 days after hatching of the first egg) [53,54]. Breeding individuals were captured by hand within nestboxes during the late incubation and early nestling-rearing stage.…”
Section: Target Species Study Area and General Field Methodsmentioning
confidence: 99%
“…Food availability during breeding can strongly affect parental investment, egg composition and, subsequently, offspring growth and condition. For example, food-supplemented birds have been found to lay larger clutches and eggs (Zanette et al, 2006a;Karell et al, 2008;Benowitz-Fredericks et al, 2013;Ruffino et al, 2014;Ruuskanen et al, 2016;Podofillini et al, 2019; but see Giordano et al, 2015a) or vary their transfer of hormones and immune factors to eggs (Gasparini et al, 2007;Benowitz-Fredericks et al, 2013;Morosinotto et al, 2016; but see Ruuskanen et al, 2016). Maternal food supplementation is also known to shorten incubation duration and lead to increased offspring mass, condition and immune defence (Pihlaja et al, 2006;Karell et al, 2008;Moreno et al, 2008;Vafidis et al, 2016;Podofillini et al, 2019; but see Verboven et al, 2003).…”
Section: Introductionmentioning
confidence: 99%